Human Resource Competency Development to Support the Development of Blue Economy-Based Marine Energy - Parashakti, Ryani Dhyan; Perkasa, Didin Hikmah; Aprillita, Dwi; Elvaresia, Meysiel; Rizky, Muhammad Alif (Ilomata International Journal of Management, 2024)
The utilization of ocean energy based on the blue economy has become a primary focus in efforts to achieve sustainability in the maritime sector. The development of this sector requires high-quality human resources to address complex challenges. Therefore, this research aims to identify the need for human resource competencies to support the development of ocean energy based on the blue economy. This study adopts a mixed-methods approach (qualitative and quantitative) with a survey of stakeholders in the ocean energy sector. The survey will be conducted to gather data on the competencies required by personnel in various fields such as technology services, management, and law. The collected data will be analyzed using factor analysis techniques to identify the most important competencies. The targeted outcome is to provide employees as future generations with additional knowledge insight into relevant blue economy aspects aligning with the needs and challenges they will face in the future. We hope that the results of this research will provide valuable information for those involved in human resource development in the ocean energy service sector. This information can be utilized to develop training and staff development programs tailored to the specific needs.